Training of Personnel in Oriental Insurance Company Limited: A Study of Regional Offices in Punjab and Haryana - Arora, Shagun; Singh, Charanjeev; Sharma, R. K. (Prabandhan: Indian Journal of Management, 2010)
Present day industry, commerce and trade depend entirely on the insurance for their operation. The banks and different financial institutions lend finances to the industrial and commercial undertaking only on the basis of the collateral security of their insurance covers. Even no bank would advance loan on the security of the property unless it is insured against loss or damage by insurable perils. Hence, insurance by covering up the risk associated with the loss of property or any financial loss encourages the commerce and trade, which leads to the economic development of the country.